Methods in Premodern Economic History Case Studies from the Holy Roman Empire, C. 1300-C. 1600 - Kypta, Ulla (Palgrave Studies in Economic History Ser., 2019)
Intro -- Contents -- Notes on Contributors -- List of Figures -- List of Tables -- 1: Introductory Remarks -- References -- 2: Grand Narratives in Premodern Economic History -- Great and Little Divergence (Julia Bruch) -- Urbanisation (Ulla Kypta) -- Population, Demography and Economic Growth (Ulf Christian Ewert) -- Commercial Revolution (Stephan Köhler, Tanja Skambraks) -- The Emergence of Capitalism (Stephan Köhler, Christian Scholl, Tanja Skambraks) -- Transaction Costs and Institutions (Ulla Kypta) -- Trust (Tanja Skambraks) -- Materiality (Julia Bruch, Tanja Skambraks) -- References -- 3: Introduction into the Study of Production -- Population (Ulf Christian Ewert) -- Labour (Niels Petersen) -- Research Topics -- Unfree Labour -- The Rise of Employment Contracts -- Payment by Geding and Time Wage in the Agrarian World -- Piece Rates and Time Wage in Urban Crafts -- Agriculture and Mining -- Manorialism and Landownership (Marco Veronesi) -- Manorialism and the Decline of Serfdom -- Rentengrundherrschaft (rent manorialism), Agrarian Capitalism and the Late Medieval Village -- Landownership -- Collective Goods, in the Middle Ages (Ulf Christian Ewert) -- Collective Goods in the Medieval World -- Definition and Typology of Collective Goods -- Problems of Provision, Maintenance and Management of Collective Goods -- Town and Country (Niels Petersen) -- Mining (Ivonne Burghardt) -- Crafts (Julia Bruch) -- Guilds -- Specialisation and Differentiation -- Knowledge and Innovation -- Services (Julia Bruch) -- References -- 4: Introduction into the Study of Markets -- Europe, c. 1300-1600: Commercialisation and the Market Economy (Angela Huang, Ulla Kypta) -- Price Data as a Historical Source (Mark Spoerer) -- The End of the Beginning: The Consumer Revolution (Eva Brugger) -- Elements of the Market (Angela Huang und Ulla Kypta).